PERNYATAAN DALAM TINDAK UJAR EKSPOSITIF PADA PIDATO OBAMA DI UNIVERSITAS INDONESIA 10 NOVEMBER 2010 (SUATU ANALISIS PRAGMATIK) - LULENG, DEMEITRIUS; KODONG, FENTJE; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled ‘’Pernyataan dalam tindak ujar Ekspositif pada pidato Obama di universitas Indonesia 10 November 2010. There are six types of statement, those are: affirming, denying, stating, describing, classing, identifying. The objectives of research are to analyze the functions of statement in expositive act of Obama speech at the university of Indonesia, November 10,2010. The data of Statement have been taken from the speech of Obama at the University of Indonesia. The research uses descriptive method supported by Austin’s theory. The result of this research shows that are six functions of statement that could be found in the speech of Obama at the university of Indonesia are affirming, denying, stating, describing, classing, identifying. Keywords: Statement in expositive act, Speech act of statement.